Ethics of undergraduate students: a study in Malaysian public universities - Rodzalan, Shazaitul Azreen; Mohamed Saat, Maisarah (2016)
This paper aims to determine the ethics of undergraduate students in four aspects of moral processes; awareness, judgement, intention and behaviour. It further explores the impact of gender and academic disciplines on these four moral processes. A total of 2000 undergraduate students from six public universities in Malaysia involved in this study. Data were collected through survey consists of 14 ethical statements developed based on previous studies. Descriptive analysis (such as mean), t-test and Analysis of Variance (ANOVA) were employed for the data analysis. Overall, results reveal that student’s ethical level was mixed. The results also demonstrate that engineering students have low level of ethics, as compared to social science and science students. In terms of gender differences, female students appear to have higher level of ethics than their male counterparts. The findings of this study provide some educational and theoretical implications.